RAIMONDICERAS RAIMONDII (GABB, 1877) (AMMONOIDEA): PRELIMINARY TAXONOMIC STUDY - Alleman Haeghebaert, Vera (2019)
A reference taxonomic collection deposited in the Department of Paleontology of the Museum of Natural History “Vera Alleman Haeghebaert” of Ricardo Palma University consists of the identifi cation, registration and description of seventeen specimens of the genus Raimondiceras Spath 1924, of which twelve specimens were attributed to the species Raimondiceras raimondii (Gabb, 1877). Th e initial taxonomic study was based on the publications of William More Gabb and Carlos Lissón. In addition, the identifi cation key of the Ammonoidea species of the Morro Solar Group, Valanginian-Hauterivian de Lima, Peru was used. Having lost all the “types”, original specimens of the species, we intend to start the complementary and updated description of the species. Th e place where Antonio Raimondi and Carlos Lissón obtained the fi rst specimens of R. raimondii was specifi ed: the La Herradura Formation outcrops in the hills of the Morro Solar de Chorrillos, Lima. Raimondiceras raimondii was found only in the La Herradura Formation.